How do consumption patterns of foreign and domestic remittance recipients and non recipients compare? Evidence from Pakistan - Junaid Ahmed; Mazhar Mughal (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2014)
This study analyzes the differential consumption patterns of foreign and domestic remittances to migrant households in Pakistan using Working-Leser framework and propensity score matching. Findings point to differing consumption behaviour across foreign and domestic recipients. Foreign remittances are considered as fungible and spent in the same way as other sources of income. In contrast, domestic remittances are considered a less permanent source of income and are spent more on improving the households' human capital.
Keywords: O12; O15; O53; 330; expenditure; consumption patterns; foreign remittances; domestic remittances; Pakistan